Colorimetric Methods for Estimation of Losartan Potassium from Tablet Formulation - Singhvi, I.; Bhatia, M.S. (Asian Journal of Chemistry, 2010)
Two simple colorimetric methods have been developed for the estimation of Losartan potassium from tablet formulation. Developed methods are based on formation of ion pair complex of drug with dyes. The first developed method is based on formation of purple coloured complex of drug with bromocresol green. The coloured complex shows absorbance maxima at 612.4 nm and obeys Beer's law in the concentration range of 30–150 μg/mL of drug. The second developed method is based on the formation of coloured complex of drug with bromophenol blue which shows absorbance maxima at 607.0 nm and linearity in the concentration range of 20–200 μg/mL of drug. Results of analysis for both the methods were validated statistically and by recovery studies.